Improper sitting posture while eating adversely affects maximum tongue pressure - Mineka Yoshikawa; Kanako Nagakawa; Reiko Tanaka; Kanako Yamawaki; Takahiro Mori; Aya Hiraoka; Chiaki Higa; Yuichi Nishikawa; Mitsuyoshi Yoshida; Kazuhiro Tsuga (Elsevier, 2021)
Background/purpose: Although many studies have examined the efficacy of neck and trunk positioning during eating, few studies have examined how the positioning of the lower extremities affects swallowing function. The purpose of this study was to examine how tongue pressure, which is an important factor during swallowing, is affected by eating postures in bed and wheelchair. Materials and methods: A total of 43 healthy adults (13 men and 30 women; 29.0 ± 5.9 years) and 33 elderly individuals requiring long-term care (14 men and 19 women; 83.6 ± 7.8 years) participated.In both healthy and elderly participants, tongue pressure was measured in four different postures: a good and poor postures in bed (postures 1 and 2, respectively), and a good and poor postures in a reclining wheelchair (posture 3 and 4, respectively). Results: Among the healthy participants, the mean tongue pressure was significantly higher in posture 1 (40.2 ± 7.24 kPa) than in posture 2 (37.6 ± 8.68 kPa) or posture 4 (38.2 ± 8.14 kPa) (P < 0.05). Tongue pressure was also significantly higher in posture 3 (41.3 ± 7.75 kPa) than in either posture 2 or 4 (P < 0.05).Among the elderly participants, the median tongue pressure in posture 1 (16.9 kPa; interquartile range [IQR], 9.4-21.6 kPa) was significantly higher than that in posture 2 (14.1 kPa; IQR, 9.2-21.6 kPa). Tongue pressure in posture 3 (18.5 kPa; IQR, 14.2-26.0 kPa) was significantly higher than that in either posture 1 or 2, and posture 4 (15.9 kPa; IQR, 10.6-22.9 kPa). Conclusion: Posture during eating can potentially affect tongue pressure.